Impact of Modifying Filler into Porous on Hydrophobicity Behaviour of The Silica-HDPE Composite - Muhammad Defrizal; Tetty Kemala; Mohammad Khotib (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Even though the approach is relatively simple and does not require additional treatment, the porous filler method has not been widely utilized to boost the composite’s hydrophobicity. Therefore, this study wants to show that silica’s porosity as a filler material affects the surface roughness and hydrophobicity of its composite (in this case, silica-HDPE). Pore formation in silica uses the soft-template method with Tween-80 as the mould. The amount of surfactant was varied by 0, 5, and 10 g. The particles are then physically composited into the HDPE matrix. Surface characterization of silica particles analyzed by Brunauer-Emmett-Teller (BET) shows enhancement in particle porosity as the amount of surfactant added is increased. When it is inserted into HDPE, the silica particles with the highest porosity have the greatest surface roughness. It is confirmed by the wavy surface texture of this composite when it is characterized using an Atomic Force Microscope (AFM). These results are accompanied by a significant enhancement in the contact angle value at each concentration. From the contact angle and AFM data, porous silica has the role of surface texture provider in raising its roughness. It affects the improvement of the hydrophobicity according to the Cassie-Baxter equation, which states that the more air fraction formed on a surface, the higher the contact angle obtained.